ISOLASI DAN PENENTUAN INDEKSHIDROLISIS BAKTERI AMILOLITIK DARI TANAH SEDIMENT MANGROVE DI WONOREJO, SURABAYA - Aliyah Siti Sundari; Ni Nyoman Purwani; Anita Kurniati (Universitas Lambung Mangkurat, 2019)
Mangrove sediment is a habitat for various bacteria, one of them is amylolytic bacteria which has the potential to produce amylase enzyme. Amylase enzyme has many benefits in industry, textiles and medical. The mangrove ecosystem area has special soil characteristics, which have the opportunity to have microorganism diversity, one of which is the mangrove ecosystem in the Wonorejo region, Surabaya. This study aims to obtain potential amylolytic bacteria from potential amylolytic isolates derived from mangrove sediment. Soil bacteria were isolated in Starch media for 2% agar and tested with Lugol’s Iodine reagents to measure their amylolytic index. Character isolates observed included colony morphology, Gram staining, and motility. Of the 27 isolates found there were 3 isolates with the highest index values in their activity, namely isolates A.7, A.27 and A.64. Characterization results showed that isolates A.7 and A.64 were Gram negative bacteria, and isolates A.27 were Gram positive bacteria. And the motility results for the three isolates were negative, with the results of a positive catalase test.